Perceived Facilitators and Barriers to Local Health Department Workers' Participation in Infectious Disease Emergency Responses. Issue 6 (November 2017) - Rutkow, Lainie; Paul, Amy; Taylor, Holly A.; Barnett, Daniel J.
Abstract : Context: Local health departments play a key role in emergency preparedness and respond to a wide range of threats including infectious diseases such as seasonal influenza, tuberculosis, H1N1, Ebola virus disease, and Zika virus disease. To successfully respond to an infectious disease outbreak, local health departments depend upon the participation of their workforce; yet, studies indicate that sizable numbers of workers would not participate in such a response. The reasons why local health department workers participate, or fail to participate, in infectious disease responses are not well understood. Objective: To understand why local health department workers are willing, or not willing, to report to work during an infectious disease response. Design: From April 2015 to January 2016, we conducted 28 semistructured interviews with local health department directors, preparedness staff, and nonpreparedness staff. Setting: Interviews were conducted with individuals throughout the United States. Participants: We interviewed 28 individuals across 3 groups: local health department directors (n = 8), preparedness staff (n = 10), and nonpreparedness staff (n = 10). Main Outcome Measures: Individuals' descriptions of why local health department workers are willing, or not willing, to report to work during an infectious disease response. Results: Factors that facilitate willingness to respond to an infectious disease emergency included availability of vaccines and personal protective equipment; flexible work schedule and childcare arrangements; information sharing via local health department trainings; and perceived commitments to one's job and community. Factors that hinder willingness to respond to an infectious disease emergency included potential disease exposure for oneself and one's family; logistical considerations for care of children, the elderly, and pets; and perceptions about one's role during an infectious disease response. Conclusion: Our findings highlight opportunities for local health departments to revisit their internal policies and engage in strategies likely to promote willingness to respond among their staff. As LHDs face the persistent threat of infectious diseases, they must account for response willingness when planning for and fielding emergency responses. Our findings highlight opportunities for local health departments to revisit their internal policies and engage in strategies likely to promote response willingness to infectious disease emergencies among their staff.